2003
DOI: 10.1002/ppul.10230
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for initial acquisition of Pseudomonas aeruginosa in children with cystic fibrosis identified by newborn screening

Abstract: The objective of this study was to identify risk factors for initial detection of Pseudomonas aeruginosa (P. aeruginosa) in children with cystic fibrosis (CF) identified by newborn screening. Life history data on 180 patients, collected prospectively in a follow-up study of infants and children diagnosed with CF, were examined for factors associated with the initial detection of P. aeruginosa ascertained by oropharyngeal cultures. Univariate and multivariate Cox proportional hazards regression analyses were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
2
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 21 publications
8
54
2
4
Order By: Relevance
“…9 Patients with cystic fibrosis become colonized and infected with nonmucoid P. aeruginosa; these strains convert to mucoid strains, on average, at a younger age in women than in men. 3,10,11 In an attempt to explain these observations, we and others have investigated the effect of the female sex hormone estradiol on airway biology. Women with cystic fibrosis appear to be at greater risk for exacerbations during periods of high circulating levels of estradiol, when airway-surface liquid is diminished and antimicrobial peptides are scarce and there is a blunted inflammatory response to microbial agonists.…”
Section: Discussionmentioning
confidence: 99%
“…9 Patients with cystic fibrosis become colonized and infected with nonmucoid P. aeruginosa; these strains convert to mucoid strains, on average, at a younger age in women than in men. 3,10,11 In an attempt to explain these observations, we and others have investigated the effect of the female sex hormone estradiol on airway biology. Women with cystic fibrosis appear to be at greater risk for exacerbations during periods of high circulating levels of estradiol, when airway-surface liquid is diminished and antimicrobial peptides are scarce and there is a blunted inflammatory response to microbial agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Gender dichotomy is recognized in CF disease, with female patients having poorer survival, worse lung function, and earlier colonization with Pseudomonas aeruginosa [6][7][8][9][10][11][12][13][14][15][16][17]. The lack of an explanation for this disparity coupled with a narrowing of the gender gap in recent times has sparked debate about whether such a gap ever existed, or whether the improvements observed can be explained by therapeutic advances or a greater compliance with therapy among female patients.…”
Section: Gender Differences In Cfmentioning
confidence: 99%
“…It does not appear to be common among children with CF detected by newborn screening in the United States (27). A study of 180 children in Colorado detected by newborn screening identified a median age of acquisition of P. aeruginosa of 8.1 years (133). In 2003, CFF issued new recommendations to minimize the risk of person-to-person transmission of infectious agents, including segregating asymptomatic patients from those with established disease (134).…”
Section: Person-to-person Transmission Of Infectious Agentsmentioning
confidence: 99%
“…An example is an evaluation by the Colorado newborn screening program relative to P. aeruginosa acquisition (133). Moreover, data collection and analysis are needed to evaluate and optimize the performance of screening and diagnostic algorithms (17).…”
Section: Risks Of Harms and Costsmentioning
confidence: 99%